Kajian Literatur Sholat Shubuh dan Implikasinya Terhadap Kebugaran Jasmani - Azzahra Aulia Sabrina; Ferdy Aland Pradana; Ma’ruf Arfiyansyah; Nadiatul Hilaliyah (Pusat Riset dan Inovasi Nasional, 2024)
This literature review explores the physical fitness implications of the Fajr prayer, analyzing the latest studies from 2020 to 2024. By examining the features of the Fajr prayer from an Islamic perspective, its benefits for physical and mental health, as well as related hadith, this study aims to provide a comprehensive understanding of its overall impact. holistic. Findings show that regular morning prayers contribute positively to overall well-being, supporting the integration of spiritual practices into daily fitness routines.